Comparison of High-grade Maitland Mobilization and Post Isometric Relaxation (PIR) Muscle Energy Technique on pain, range of motion, and functional status in patients with Adhesive Capsulitis - Sehrish Naureen, Amna Zia, Maira Amir, Faiqa Mehmood Rana, Umme Habiba (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To compare the effect of post isometric relaxation (PIR) muscle energy technique and high-grade Maitland mobilization technique on pain, glenohumeral joint abduction and external rotation, and functional activities in the subject of frozen shoulder. Study design: Randomized control trial Methods: A total of 60 patients were initially assessed for eligibility and 52 were included in the study after taking written consent. Patients were divided into two groups; Group A was treated with post isometric relaxation (PIR) technique and group B with Maitland grade (IV) mobilization for 4 weeks. Pain with a Numeric Pain rating scale, Glenohumeral joint abduction and external range of motion with a goniometer and shoulder function with shoulder pain and disability index were evaluated. Results: Both groups were similar at baseline (p> 0.05) and within-group comparison has shown that there was a significant improvement in all variables in both groups as p<0.05, but between-group comparison has shown that post-isometric relaxation (PIR) was more effective in reducing pain, improving range of motion and functional status and the mean difference between both groups for pain was 1.96, for shoulder abduction was 24.88, for external rotation was 10.42 and for SPADI was 23.27 with p<0.05 for all, showing that post isometric relaxation (PIR) muscle energy technique is superior to the Maitland grade IV mobilization technique in improving pain, Glenohumeral joint range, and shoulder function. Conclusion: Both Post isometric relaxation (PIR) and Maitland Mobilization are effective but post isometric relaxation (PIR) muscle energy technique is superior to the Maitland grade IV mobilization technique in improving pain, Glenohumeral joint range, and shoulder function. Keywords: Adhesive capsulitis, Maitland mobilization technique, Muscle energy technique, Shoulder pain and disability